Dataset relating to Arsenic contamination of rainfed versus irrigated rice - Ingram, Ben; Kirk, Guy J. D.; Corstanje, Ronald; Simmons, Robert W. (Cranfield University, 2025)
Arsenic (As) contamination of rice remains a major human health issue in Asia. Most research has been on irrigated rice. However much of the projected increase in global rice demand over coming decades must be met by rainfed lowland systems, for which As relations are poorly understood. We present the most comprehensive survey to date of As in rice in farmers’ fields across Bangladesh, covering both irrigated and rainfed systems. We collected rice grain and soil at 943 sites in the three rice growing seasons: irrigated Boro, rainfed Aus, and longer-duration rainfed Aman. Grain As concentrations increased in the order Aman << Boro < Aus with 2, 25 and 41 % of the sites exceeding permitted thresholds, respectively. The greater concentration in Aus than Boro challenges the accepted wisdom that contaminated irrigation water is the main source of As. The main growth and grain filling periods, when most As is taken up, coincide in Aus with the peak of the monsoon rains, suggesting a link between rainfall and high grain As. We suggest this is due to stronger soil reducing conditions and hence As solubility during peak rainfall. We discuss implications for rainfed lowland rice across Asia and mitigation options.
Data from rice grain analysis, containing 75 variables and 939 samples. A full description of each of the columns is included in the Ingram2025-Dataset_Description.txt file.
Keywords: biogeochemical cycling; geohazard; field survey; paddy soil; rice intensification